2016
DOI: 10.18632/oncotarget.7578
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 downregulation leads to breast cancer progression via LncRNA-MALAT1 regulation and CDK4/E2F1 signal activation

Abstract: The long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been recently shown to be dysregulated in several cancers. However, the mechanisms underlying the role of MALAT1 in breast cancer remain unclear. Herein, we showed that MALAT1 was aberrantly increased in breast cancer tissues and cells. MALAT1-siRNA inhibited breast cancer cell proliferation and cell cycle progression in vitro and in vivo. Furthermore, MALAT1 acted as an endogenous potent regulator by directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
2
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 39 publications
(50 reference statements)
4
84
2
5
Order By: Relevance
“…In the present study, our results indicated that MALAT1 expression was up-regulated in multiple breast cancer cell lines compared with normal breast cell line, as well as in ER-positive breast cancer tissues compared with adjacent normal breast cancer tissues. These data correlated with previous studies indicating that MALAT1 was overexpressed in primary breast cancer and promoted proliferation of breast cancer cells [2729]. We identified for the first time that MALAT1 expression was correlated with ER and its target genes in breast cancer, providing a new perspective in MALAT1 function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, our results indicated that MALAT1 expression was up-regulated in multiple breast cancer cell lines compared with normal breast cell line, as well as in ER-positive breast cancer tissues compared with adjacent normal breast cancer tissues. These data correlated with previous studies indicating that MALAT1 was overexpressed in primary breast cancer and promoted proliferation of breast cancer cells [2729]. We identified for the first time that MALAT1 expression was correlated with ER and its target genes in breast cancer, providing a new perspective in MALAT1 function.…”
Section: Discussionsupporting
confidence: 90%
“…Bamodu et al identified MALAT1 as a mediator of KDM5B oncogenic potential in triple-negative breast cancer, and could be reversed by hsa-miR-448 [30]. Furthermore, MALAT1 reversed the inhibitory effect of miR-124 on breast cancer proliferation and was involved in the cyclin-dependent kinase 4 (CDK4) expression [29]. …”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can function as oncogenes or tumor suppressor genes in cancer, aiming at restoration of tumor suppressor genes and silence of oncogenes would be a novel anticancer therapy (23). The inhibitory effect of miR-124 in tumor growth and migration, as well as dysregulation of miR-124 has been reported in various tumor types (6)(7)(8)(9). In a previous (13) and the present study, miR-124 was downregulated in GC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, miR-124 has been found down-regulated in multiple tumor types, including cancer (6), prostate (7), lung (8) and colorectal cancer (9). It also been found that miR-124 could inhibit the proliferation of GC cells proliferation by targeting Rho-associated protein kinase 1, enhancer of zeste homolog 2 (EZH2) and sphingosine kinase 1 (SPHK1) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…CDK4 is overexpression in several cancer comprising of breast cancer, pancreas cancer, clear cell renal cell carcinoma, and colorectal cancer [2023]. Downregulation of MALAT1 (long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1) inhibits breast cancer cell proliferation and cell cycle progression in vitro and in vivo through miR-124 downregulation and CDK4 upregulation [20, 24]. Overexpression of cyclin D1/CDK4 is regulated by CEACAM6 and promotes cell proliferation in human pancreatic carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%